Cover Feature: Cyclic(Alkyl)(Amino)Carbene (CAAC)‐Supported Zn Alkyls: Synthesis, Structure and Reactivity in Hydrosilylation Catalysis (Chem. Eur. J. 34/2019). Issue 34 (9th May 2019) - Bruyere, Jean‐Charles; Specklin, David; Gourlaouen, Christophe; Lapenta, Rosita; Veiros, Luis F.; Grassi, Alfonso; Milione, Stefano; Ruhlmann, Laurent; Boudon, Corinne; Dagorne, Samuel
Abstract : The reactivity of cyclic(Alkyl)(amino)carbenes (CAACs) with ZnMe2 was studied. While adduct (CAAC)ZnMe2 is highly reactive (to undergo a Zn−Me migration reaction), robust two‐coordinate (CAAC)ZnR + Lewis acidic cations were also prepared and characterized. Cation (CAAC)ZnC6 F5 + is an effective and selective catalyst for alkene, alkyne and CO2 hydrosilylation. Its overall reactivity is essentially under charge control as it is only slightly affected by the electronic differences between CAAC and Arduengo‐type NHC ligands. More information can be found in the Full Paper by S. Dagorne et al. on page 8061 .